Dhikr as Anxienty Therapy: A Solution to The Problems Faced by Modren Society in a Viewpoint of Tafseer fi Zilal Al-Quran by Sayyid Qutb - Affandi, Yuyun; Fitri, Ahmad Asrof; Alfandi, M.; Sulaiman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This article is intended to find out:1) how the interpretation of Sayyid Qutb regarding dhikr contained in Tafseer Fi Zilal al-Quran is, 2) how dhikr as an anxiety therapy for modern society problems in viewpoint of Sayyid Qutb in the context of current social life is. This study used a library research using descriptive qualitative approach. The study results showed: 1) The interpretation of Sayyid Qutb regarding dhikr as stated in the Tafseer Fi zilal al-Qur'an has various meanings. Among the meanings are a) remembering, b) prayer, c) calling the name of Allah, d) lessons/wisdom, e) thinking of natural phenomena, f) knowledge, g) warnings, h) the books of Allah. 2) dhikr as an anxiety therapy for the modern society problems in viewpoint of Sayyid Qutb in the current context of social life is dhikr has several functions in the context of anxiety therapy for the Islamic individuals, including: the function of a) prevention, b) guidance, and c) treatment.